Substantial improvements of long-term stability in encapsulation-free WS2 using highly interacting graphene substrate. (1st December 2016) - Kim, Se-Yang; Kwak, Jinsung; Kim, Jung Hwa; Lee, Jae-Ung; Jo, Yongsu; Kim, Sung Youb; Cheong, Hyeonsik; Lee, Zonghoon; Kwon, Soon-Yong
Abstract: We report the novel role of graphene substrates in obstructing the aging propagation in both the basal planes and edges of two-dimensitional sheets of transition metal dichalcogenides (TMDs). Even after 300 d in ambient air conditions, the epitaxially grown WS2 /graphene samples have a clean, uniform surface without any encapsulation. We show that high crystallinity is an effective factor that determines the excellent air stability of WS2 /graphene, and we present impressive experimental evidence of the relation between defects and the aging phenomena. Moreover, we reveal the strong interlayer charge interaction as an additional factor for the enhanced air stability as a result of charge transfer-induced doping. This work not only proposes a simple method to create highly stable TMDs by the selection of a suitable substrate but also paves the way for the realization of practical TMDs-based applications.